Reflecting the Concept of Family in Turkish and American Societies through Proverbs: The Masnavi and Poor Richard’s Almanack - Baykara, Tuba; Kaçmaz, Ercan (My University, 2022)
In this study the proverbs on the concept of family in the works of Mawlana and Benjamin Franklin, important personalities of their time, are analyzed. Mawlana's The Masnavi and Franklin's Poor Richard's Almanack are the main texts used in this study. Proverbs, which are seen as inseparable parts of culture, are widely used in both works. With this article, it is planned to shed light on the concept of family with a comparative study through proverbs. While the proverbs about the concept of family are discussed, the words related to the family such as husband-wife, woman-man, mother-father, children, marriage, and love are examined in detail. The positive and negative aspects of the proverbs used when dealing with the characteristics, duties and responsibilities of the two historic figures are compared. Subsequently, while examining the relations of women, men, and family, light is shed on the important points in the views of both communities on these relations. This study, which deals with proverbs and cultural differences, is expected to contribute to studies on Turkish and American culture.